Asthma Patients Benefit More Than Chronic Obstructive Pulmonary Disease Patients in the Coronavirus Disease 2019 Pandemic - Xiong, Ruoyan; Zhao, Zhiqi; Lu, Huanhuan; Ma, Yiming; Zeng, Huihui; Chen, Yan (Frontiers in Medicine, 2021)
Background: Coronavirus disease 2019 (COVID-19) has raised many questions about the role of underlying chronic diseases on disease outcomes. Despite this, there is limited information on the effects of COVID-19 on chronic airway diseases. We conducted the present study to address the impact of COVID-19 on patients with asthma or chronic obstructive pulmonary disease (COPD) and ascertain the risk factors of acute exacerbations (AEs). Methods: This single-center observational study was conducted at the Second Xiangya Hospital of Central South University and involved asthma or COPD patients who had been treated for at least a year before the COVID-19 pandemic with inhaled combination corticosteroids (ICSs), budesonide, and one long-acting beta-2-agonist (LABA), formoterol. We conducted telephone interviews to collect demographic information and clinical data between January 1, 2019, and December 31, 2020, focusing on respiratory and systemic symptoms and times of exacerbations. The data for asthma and COPD were compared, and the risk factors for AEs were identified using logistic regression analysis. Results: A total of 251 patients were enrolled: 162 (64.5%) had asthma, 89 had COPD, and none had COPD/asthma overlap. The frequency of AEs among asthma patients was lower in 2020 than in 2019 (0.82±3.33 vs. 1.00±3.16; P<0.05). Moreover, asthma patietns visited the clinic less (0.37±0.93 vs. 0.49±0.94; P<0.05) and used emergency drugs less (0.01±0.11 vs. 007±0.38; P<0.05) in 2020. In contrast, among COPD patients, there were no significant differences in AE frequency, clinic visits, or emergency drug use. Logistic regression analysis showed that a history of at least one AE within the last 12 months was associated with increased AE odds for both asthma and COPD during the COVID-19 pandemic (odds ratio: 13.73, 95% CI: 7.04–26.77; P<0.01). Conclusion: During the COVID-19 pandemic, patients with asthma showed better disease control than before, while those with COPD may not have benefited from the COVID-19 pandemic. For both asthma and COPD, at least one AE within the previous 12 months was a risk factor for AEs during the COVID-19 pandemic. Among asthma patients, the risk factors for AE during the COVID-19 pandemic were urban environment, smoking, and lower asthma control test scores.